2019
DOI: 10.52358/mm.vi2.95
|View full text |Cite
|
Sign up to set email alerts
|

Analyse, développement et évaluation d'une formation médicale en ligne

Abstract: Dans le cadre d’un projet intitulé Evaluation of a context-adapted wiki-based decision aid supporting critically ill patients’ decisions about life-sustaining therapies, financé par le Réseau canadien des soins aux personnes fragilisées, l’équipe de conception pédagogique de la Société pour l’apprentissage à vie (SAVIE) s’est joint au projet de recherche afin de développer une formation en ligne destinée aux médecins, aux étudiantes et aux étudiants tenant compte d’un certain nombre d’exigences techniques comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We found that EPs' and ACHPs' intention to use wiki-based knowledge tools can be predicted by the three direct TPB constructs-attitude toward the behavior, SN, and PBC. We have also identified the salient beliefs that will help us develop a theory-based training program to promote the use of wiki-based knowledge tools in trauma care centers for EPs and ACHPs [40,73]. These salient beliefs will also inform the development of interventions that support the implementation of future wiki-based knowledge tools for other acute care contexts, such as optimal ED elder care [74] and pandemic knowledge management [75].…”
Section: Principal Findingsmentioning
confidence: 99%
“…We found that EPs' and ACHPs' intention to use wiki-based knowledge tools can be predicted by the three direct TPB constructs-attitude toward the behavior, SN, and PBC. We have also identified the salient beliefs that will help us develop a theory-based training program to promote the use of wiki-based knowledge tools in trauma care centers for EPs and ACHPs [40,73]. These salient beliefs will also inform the development of interventions that support the implementation of future wiki-based knowledge tools for other acute care contexts, such as optimal ED elder care [74] and pandemic knowledge management [75].…”
Section: Principal Findingsmentioning
confidence: 99%